2022
DOI: 10.1093/bioinformatics/btac517
|View full text |Cite
|
Sign up to set email alerts
|

SpikePro: a webserver to predict the fitness of SARS-CoV-2 variants

Abstract: Motivation The SARS-CoV-2 virus has shown a remarkable ability to evolve and spread across the globe through successive waves of variants since the original Wuhan lineage. Despite all the efforts of the last two years, the early and accurate prediction of variant severity is still a challenging issue which needs to be addressed to help, for example, the decision of activating COVID-19 plans long before the peak of new waves. Upstream preparation would indeed make it possible to avoid the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To investigate the impact of A475V on the overall fitness of BA.5, we utilized SpikePro, a recently developed structure-based computational tool designed to predict the viral fitness of a variant based on its spike protein sequence ( 21 , 22 ). Our analysis of the prediction data revealed that the presence of a single A475V substitution in the spike protein resulted in improved immune escape from convalescent plasma ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the impact of A475V on the overall fitness of BA.5, we utilized SpikePro, a recently developed structure-based computational tool designed to predict the viral fitness of a variant based on its spike protein sequence ( 21 , 22 ). Our analysis of the prediction data revealed that the presence of a single A475V substitution in the spike protein resulted in improved immune escape from convalescent plasma ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the ability of the benchmarked methods to predict the known epitopes in the spike protein, we gathered 83 spike protein-antibody complexes resolved by X-ray crystallography or cryo-electron microscopy and deposited in the PDB [5] (see [57,58] for the list of PDB ids). We extracted 83 epitopes from these complexes; 75 of them are localized on the RBD of the spike protein, while the remaining eight target its N-terminal domain (NTD).…”
Section: Sars-cov-2 Case Studymentioning
confidence: 99%
“…For the interaction between the RBD in the spike protein and the host receptor (ACE2) is critical in the invasion of virus, both the Peptide Inhibition Covid 19 Repository [105] and the SARS-CoV-2 Interactome 3D [106] visualize the interaction between RDB and ACE2, facilitating further exploration of this mechanism. Mutations present on the spike protein are likely relevant to viral adaptation and immune escape, SpikePro enables a rapid prediction of the adaptation of some mutant based on the structural models [107] . VirHostNet contains a relatively complete virus-host protein interaction resources that facilitates target determination and drug design [108] .…”
Section: Virus-host Interaction and Pathway Researchmentioning
confidence: 99%